2019
DOI: 10.1111/apa.15072
|View full text |Cite
|
Sign up to set email alerts
|

Examining perinatal subdural haematoma as an aetiology of extra‐axial hygroma and chronic subdural haematoma

Abstract: Aim Benign external hydrocephalus (BEH), hygroma and chronic subdural haematoma are extra‐axial fluid collections in infants. MRI studies have shown that almost half of all new‐borns have perinatal subdural blood, generally referred to as subdural haematoma (SDH) or perinatal SDH. Epidemiologically there are striking similarities between chronic SDH and BEH in infants. Methods Discussion of pathophysiological mechanisms for BEH and chronic SDH, based on existing literature. Results Perinatal SDH is common, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 92 publications
0
15
0
2
Order By: Relevance
“…In other words, the ad hoc closure clause, that all relevant medical conditions have been excluded, is certainly false. This is supported by the non-shaken baby theory by Geddes et al and benign external hydrocephalus (Geddes, Vowles, Hackshaw, Nickols, Scott, & Whitwell, 2001;Geddes, Tasker, Adams, & Whitwell, 2004;Zahl, Wester, & Gabaeff, 2020).…”
Section: Auxiliary Hypotheses Initial Conditions and Closure Clausesmentioning
confidence: 67%
See 3 more Smart Citations
“…In other words, the ad hoc closure clause, that all relevant medical conditions have been excluded, is certainly false. This is supported by the non-shaken baby theory by Geddes et al and benign external hydrocephalus (Geddes, Vowles, Hackshaw, Nickols, Scott, & Whitwell, 2001;Geddes, Tasker, Adams, & Whitwell, 2004;Zahl, Wester, & Gabaeff, 2020).…”
Section: Auxiliary Hypotheses Initial Conditions and Closure Clausesmentioning
confidence: 67%
“…Finally, claims that a caregiver is lying if he/she cannot explain why the infant has developed the triad signs and symptoms may seem reasonable-but only if the OUAHT theory with all its ad hoc hypotheses and clauses are presupposed to be true, or at least truth-like. They are, however, contradicted by biomechanical studies, as well as by several non-shaken baby theories, which indicate that the triad might develop spontaneously, or represents the sequelae of a delivery-associated SDH (Zahl, Wester, & Gabaeff, 2020). In other words, in triad cases without signs of external trauma, no obvious events have necessarily occurred prior to the infant´s collapse.…”
Section: Auxiliary Hypotheses Initial Conditions and Closure Clausesmentioning
confidence: 97%
See 2 more Smart Citations
“…Disagreement still exists as to whether BEH is a risk factor or not. 76,77 A recent review investigated the similarities between SDH and BEH, and presented a unifying theory of pathophysiology behind these subdural collections 78 Few neuroimaging studies have reported findings of ruptured bridging veins, except the ones reviewed above. Findings such as the tadpole or lollipop signs lack pathologic verification of bridging vein injuries.…”
Section: Discussionmentioning
confidence: 99%